Understanding the Experiences of Survivors of Sexual Violence Who Experience Silence - Naomi Putri Bahari Simeon (SEAN Institute, 2022)
This research was conducted to understand the experiences of survivors of sexual violence who experience silence. In addition, the purpose of this research is also to find out the forms of silence received by survivors of sexual violence who have tried to open up their experiences and understand the reasons that cause women's oppression in society. The research method used is a qualitative method with an interpretive phenomenological approach by Maurice-Marleu-Ponty with a critical paradigm. The theory used in this research is muted group theory from Cheris Kramarae and Alison Jaggar's analysis of radical feminism. The results found in this study are survivors of sexual violence, both those who have never and have ever spoken about their experiences, still experience silence in the form of intimidation and threats from perpetrators, victim blaming and ridicule, control or power relations or male domination, fear and anxiety about community stigma. Women are always put in the wrong position even though they have made efforts to speak to assistants and public forums.